Tanggungjawab Negara Terhadap Pelanggaran Hak Asasi Manusia Berat - Alessandro Willem Selfiano Everhard Kuhuparuw; Lucia Charlota Octavina Tahamata; Dyah Ridhul Airin Daties (PATTIMURA Law Study Review, 2023)
Gross human rights violations have been regulated in Law Number 39 of 1999 concerning Human Rights and Law Number 26 of 2000 concerning Human Rights Courts. But in reality, gross human rights violations still occur in Indonesia, one of which occurred in South Aceh known as the Jambo Keupok tragedy. The Jambo Keupok tragedy began with information conveyed by an informant to TNI members that Jambo Keupok Village became the base of the Free Aceh Movement (FAM). International law has provided a solid foundation for effective punishment of perpetrators gross violations of human rights, among others Article 4 of the Convention Against Torture and Other Cruel; In Human or Degrading Treatment or Punishment and According to Article 17 paragraph (1) of the Rome Statute of 1998, the government's responsibility regarding gross human rights violations in Jambo Keupok Aceh proceeded very slowly. This is influenced by 2 main things, namely: there is no official recognition in the Indonesian government that the event was a gross human rights violation and the second because of the Aceh tsunami disaster. After the Aceh tsunami, the Indonesian government has carried out reconciliation. Finally, in 2023, the Government of Indonesia, in this case, President Jokowidodo has determined that the Jambo Keupok Aceh incident is a gross human rights violation.